Feminisms and Gendered Dynamics of Whistleblowing: How Organisational Culture Shapes Women’s Ethical Decisions - Maulidi, Ach (Universitas Negeri Semarang, 2025)
Purpose : The study examines the feminist perspectives and gendered dynamics of whistleblowing within Indonesian local governments. Unlike previous research that largely centers on the causal link between gender and whistleblowing behavior, this study delves deeper into the structural, psychological, and cultural barriers that hinder women from reporting misconduct. Method : The study employed a qualitative approach by interviewing retired civil servants using open-ended questions to elicit detailed narratives about their experiences and perceptions. The collected data were analysed using a thematic approach based on themes that emerged during the interview process. Findings : The findings suggest that women hesitate to blow the whistle due to group-oriented thinking, loyalty obligations, perceived innocence of wrongdoers, financial dependence, emotional burdens, and vulnerability to coercion. Novelty : Theoretically, this study fills a gap in empirical research on whistleblowing and gender in non-Western, collectivist settings. It highlights the need to contextualize rational action theory. It is because the decisions to report fraud are influenced not just by legal and ethical considerations but by social harmony, hierarchy, and conformity. Practically, the findings urge organizations to create inclusive whistleblowing systems that address gender norms, enhance protections, and promote an ethical culture that supports speaking out.